Diagnostic Approach to Hereditary Colorectal Cancer Syndromes - Kalady, Matthew F.; Heald, Brandie (Clinics in Colon and Rectal Surgery, 2015)
Approximately 5 to 10% of colorectal cancers develop within a known hereditary syndrome. Specific underlying genetic mutations drive the clinical phenotype and it is imperative to determine the genetic etiology to provide meaningful surveillance and intervention. Recognizing potential patients and families with a hereditary predisposition is the first step in management. Syndromes can be categorized according to polyp burden as polyposis or nonpolyposis. Clinical assessment should start with a personal and family medical history, physical examination, and evaluation for the presence and type of colorectal polyps or cancers. Key information is gained from these simple steps and should guide the specific genetic analysis for diagnosis. Genetic counseling is a critical component to any hereditary colorectal cancer program and should be conducted before genetic testing to provide education about the implications of test results. This review focuses on the thought process that drives initial clinical evaluation and guides genetic testing for patients with suspected hereditary colorectal cancer syndromes.
Keywords: hereditary colorectal cancer syndromes; familial adenomatous polyposis; genetic testing; Lynch syndrome; hereditary nonpolyposis colorectal cancer; MYH-associated polyposis